Pengaruh Digital Literacy Terhadap Kesiapan Berwirausaha di Era-digital Mahasiswa Fakultas Ekonomi Universitas Negeri Padang - Sandria Nuwirati Almi; Elvi Rahmi (Jurnal Ecogen, 2020)
This research aims to explain the effect of digital literacy partially on entrepreneurial readiness in the digital era of Economics Faculty students, Padang State University.Type of research is associative descriptive. The study population was of Economics Faculty students, Padang State University, totaling 1579 people. The sampling technique used was proportional to random sampling, and the technique obtained 94 students as samples. The technique used in data collection is a questionnaire. The data analysis method used is a simple regression analysis. The coefficient of determination (R2) indicates that 15.1% entrepreneurship readiness of Economics Faculty students, Padang State University is influenced by digital literacy, while the remaining 84.9% is influenced by variables not examined in this research. Therefore, it is expected that researchers can then examine other variables beyond the variables that have been studied to obtain more varied results to increase entrepreneurial readiness. Regarding digital literacy, students are expected to be able to maintain and improve communication and collaboration skills so that information related to entrepreneurship obtained on the internet can be better utilized.Keywords: digital literacy, entrepreneurship readiness